Psychoanalysis and cinema: application of film analysis for learning the concept of the unconscious (Psicologia USP, 2021)
Based on the academic observation of the importance of teaching-transmitting psychoanalysis at the university, this article aims to show how much the learning of the psychoanalytic concept – unconscious – can be facilitated through the cinematographic language. For such purpose, theoretical research and psychoanalytic film analysis were chosen as research methods, these guided by applied psychoanalysis. Films consecrated by the media are used, ranging from Alfred Hitchcock’s Psycho to Tim Burton’s Alice in wonderland to set in motion the psychoanalytical conceptualization that organizes the concept of the unconscious in Freud and Lacan. It is observed, therefore, that the Freudian novelty consisted of uncoupling the unconscious from consciousness and elevating it to the status of a psychiatric instance that is expressed through dreams, flawed acts, jokes and others. From this conception, Lacan later proposes the unconscious structured as a language providing the fundamental thread of social ties.